2017
DOI: 10.1002/ppp.1933
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Sensitivity of Carbon Storage in Permafrost of North-Eastern Yakutia

Abstract: Organic carbon derived from permafrost can provide a substrate for greenhouse gas production where the buried carbon pool thaws and mobilizes into biogeochemical cycles. Much attention has focused on the permafrost carbon of the Yedoma region of Siberia due to the wide distribution of organic and ice‐rich deposits. Here, we present a new estimation of carbon storage in the upper 25 m of permafrost in north‐eastern Yakutia based on a novel database of total carbon (TC) content, bulk density and ice content of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…The data on the yields of alkali‐extracted OM (Table , Figure ) obtained in this study have shown much higher content of this OM in the alas core as compared to the yedoma core. These data are consistent with published results on the higher total carbon density in alas as compared to yedoma layers in the Kolyma River Basin (Shmelev et al, ; Webb et al, ). The higher rates of recent (Holocene) accumulation of OC within the alas sediment formed in the thermokarst lake might account for this difference (Anthony et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The data on the yields of alkali‐extracted OM (Table , Figure ) obtained in this study have shown much higher content of this OM in the alas core as compared to the yedoma core. These data are consistent with published results on the higher total carbon density in alas as compared to yedoma layers in the Kolyma River Basin (Shmelev et al, ; Webb et al, ). The higher rates of recent (Holocene) accumulation of OC within the alas sediment formed in the thermokarst lake might account for this difference (Anthony et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…This makes yedoma deposits particularly susceptible to rapid thaw during warmer climatic periods. The thaw of yedoma over Holocene history leads to its local subsidence giving rise to formation of thermokarst lakes (Shmelev et al, ). The studies on evolution of the thermokarst lakes (Anthony et al, ) have shown their changing role in CH 4 and CO 2 emission: starting from strong CH 4 emission during thaw of Pleistocene yedoma sediments, followed by strong CO 2 uptake due to high primary productivity leading to formation of organic‐rich Holocene sediments, and finally by establishing neutral (peatland type) gaseous exchange of alas sediments formed as a result of complete drain and refreezing of Holocene sediments.…”
Section: Introductionmentioning
confidence: 99%
“…The region is mostly flat terrain and consists of different geological regions [74] ( Figure 5). The western and southern part is dominated by fine-grained and ice-rich late Pleistocene yedoma deposits interspersed with thermokarst basins and river valleys and an abundance of thermokarst lakes and basins (Yedoma-Alas Complex) [75].…”
Section: Kolyma Lowland (Kol)mentioning
confidence: 99%
“…The average carbon density of deep permafrost from yedoma deposits in the Y4 watershed (13.5 kg C m −3 ) was similar to values reported for yedoma in pan-Arctic summary studies (10 +7/−6 kg C m −3 , Strauss et al, 2013;13.0 ± 0.75 kg C m −3 after correction for ice volume, Walter Anthony et al, 2014) and at taiga sites within 100 km of Chersky (12.3-15.4 kg C m −3 after correction for ice volume, Walter Anthony et al, 2014, and references therein; 14.3 kg C m −3 , Shmelev et al, 2017). Carbon density was almost twice as high in the alas, which is consistent with findings indicating that alas and thermokarst soils store substantially more 4290 E. E. Webb et al: Variability in above-and belowground carbon stocks C (∼ 40-70 %; Walter Anthony et al, 2014;Strauss et al, 2013;Siewert et al, 2015) than undisturbed yedoma, a difference that is likely due to higher rates of recent (Holocene) C accumulation at the alas site (Walter Anthony et al, 2014).…”
Section: Variability Of Soil C Poolsmentioning
confidence: 99%